2017
DOI: 10.3390/soils1010005
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal Fungi and Mineral Interactions in the Rhizosphere of Scots and Red Pine Seedlings

Abstract: Ectomycorrhizal fungi and associated bacteria play a key role in plant-driven mineral weathering and uptake of mineral-derived nutrients in the rhizosphere. The goal of this study was to investigate the physical and chemical characteristics of bacteria-fungi-mineral interactions in biofilms of Scots and red pine rhizospheres. In three experiments, seedlings were grown in columns containing silica sand amended with biotite and calcium-feldspar, and inoculated with pure cultures of ectomycorrhizal fungi or a soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 69 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…However, the role of mycorrhizas in acquiring essential resources from depth, particularly water in meaningful quantities, is still uncertain. Some work has demonstrated that rhizosphere microbes facilitate mineral weathering and, as a result, nutrient uptake (Balogh‐Brunstad et al , ), but more research is needed that to directly quantify the functional diversity of root‐associated microbes at depth and their role in plant nutrient acquisition. Oeser et al () offered a step in that direction, by quantifying the abundance – but not the functional roles – of bacterial and archaeal communities in weathered rock across several sites along a climatic gradient in the Chilean cordillera.…”
Section: Elements Sourced From Weathered Bedrock and Dust Determine Ementioning
confidence: 99%
“…However, the role of mycorrhizas in acquiring essential resources from depth, particularly water in meaningful quantities, is still uncertain. Some work has demonstrated that rhizosphere microbes facilitate mineral weathering and, as a result, nutrient uptake (Balogh‐Brunstad et al , ), but more research is needed that to directly quantify the functional diversity of root‐associated microbes at depth and their role in plant nutrient acquisition. Oeser et al () offered a step in that direction, by quantifying the abundance – but not the functional roles – of bacterial and archaeal communities in weathered rock across several sites along a climatic gradient in the Chilean cordillera.…”
Section: Elements Sourced From Weathered Bedrock and Dust Determine Ementioning
confidence: 99%